Prayer Sign as a Marker of Increased Ventilatory Hours, Length of Intensive Care Unit and Hospital Stay in Patients Undergoing Coronary Artery Bypass Grafting Surgery - Kundra, Tanveer Singh (Ann Card Anaesth, 2017)
CONTEXT: Various predictors have been used to predict diabetic patients who are likely to have increased ventilatory hours and an increased length of stay (LOS) in the Intensive Care Unit (ICU) as well as in the hospital after undergoing coronary artery bypass grafting (CABG) surgery, for example, glycosylated hemoglobin (HbA1c). The authors propose a simple bed-side test, i.e., the prayer sign to predict increased ventilatory hours and increased length of ICU and hospital stay. AIMS: The aim of the present study was to assess whether any association exists between a positive prayer sign and increased ventilatory hours, length of ICU and hospital stay after CABG surgery in diabetic patients. SETTINGS AND DESIGN: This prospective observational study was conducted in a 650-bedded tertiary cardiac center. SUBJECTS AND METHODS: A total of 501 diabetic patients were recruited in the study over a period of 1 year. Group P consisted of 121 patients with prayer sign positive, whereas Group N consisted of 380 patients with prayer sign negative. HbA1c levels, ventilatory hours, LOS in the postoperative ICU and hospital were compared. STATISTICAL ANALYSIS USED: Unpaired Student's t-test was used to compare the data. RESULTS: The mean HbA1c levels in Group P were 8.01 ± 2.28% as compared to 6.52 ± 2.46% in Group N (P < 0.0001). The mean ventilatory hours in Group P were 9.52 ± 6.46 h, and in Group N were 7.42 ± 8.01 h (P = 0.013). Whereas, the mean length of ICU stay and hospital stay in Group P was 156.42 ± 32.66 h (6.51 ± 1.36 days) and 197.36 ± 32.46 h (8.22 ± 1.35 days), respectively, it was 121.12 ± 29.48 h (5.04 ± 1.22 days) and 178.52 ± 28.52 h (7.43 ± 1.18 days) in Group N (P < 0.0001). CONCLUSIONS: A positive prayer sign is a useful bedside test for predicting increased ventilatory hours and increased length of ICU and hospital stay after CABG surgery.